Comparative Study of Environmental Disclosure in Indonesia and Malaysia: Testing Company Characteristics - Rudi Zulfikar (FEB Universitas Sultan Ageng Tirtayasa, 2021)
There are two purposes of this study. The first is to compare the environmental disclosure practices in the annual report of Indonesian and Malaysian manufacturing companies. The second is to test the impact of firm characteristics on environmental disclosure, both in Indonesia and Malaysia. Firm characteristics are represented by firm size, profitability, liquidity, firm age, and audit firm size.Under the Slovin’s Formula and purposive sampling method, 82 Indonesian and 167 Malaysian manufacturing companies are selected. Dichotomy approaches are used to measure the dependent variable of environmental disclosure. There are 9 main aspects which include 30 items of environmental according to Sustainable Reporting Guidelines version 3.1. Different proxies consist of the natural logarithm of total assets, return on equity ratio, current ratio, the natural logarithm of firm age, and audit firm size (BIG 4 and Non-Big 4) is used as a measurement of the independent variable of firm characteristics. Comparison and relation in this study tested by analysis of descriptive statistics, t-test, and multiple regression.A score of environmental disclosure both in Indonesia and Malaysia is only 18,33%. The result indicates that the environmental awareness of businessmen in manufacturing companies still low. The result of the t-test shows that there is a difference in environmental disclosure between Indonesia and Malaysia. The multiple regression analysis shows that firm size, audit firm size, and firm age are significant predictors of environmental disclosure both in Indonesia and Malaysia. Profitability and liquidity show no influence on environmental disclosure in both countries.